Citation Analysis of PJCR Humanities Journals during 2003-2007 - Roya Maghsoudi Daryeh (Iranian Journal of Information Processing & Management, 2011)
By using citation analysis, this article has studied humanities journals of Persian Journal Citation Report (PJCR) during 2003-2007. In this research "Impact Factor" and "Immediacy Index" of these journals were investigated and top publishers were determined according to the Impact Factor indicator. Findings showed that more than 75% of these journals have Impact Factor during mentioned years, while only 30% journals have Immediacy Index. Comparing the average Impact Factor of humanities journals with other fields showed the higher Impact Factor in this field.